Blocking Interleukin-33 Alleviates the Joint Inflammation and Inhibits the Development of Collagen-Induced Arthritis in Mice - Yan Li; Yeqin Fu; Huan Chen; Xiaojin Liu; Mingcai Li (Journal of Immunology Research)
Rheumatoid arthritis (RA) is considered a systemic chronic inflammatory joint disease characterized by chronic synovitis and cartilage and bone destruction. Interleukin-33 (IL-33) is a proinflammatory cytokine which is highly expressed in the synovium of RA patients and the joints of mice with collagen-induced arthritis (CIA) and exacerbates CIA in mice. However, the role of the IL-33-neutralizing antibody in the murine model of CIA remains unclear. In the present study, CIA mice were given intraperitoneally with polyclonal rabbit anti-murine IL-33 antibody (anti-IL-33) or normal rabbit IgG control after the first signs of arthritis. Administration of anti-IL-33 after the onset of disease significantly reduced the severity of CIA and joint damage compared with controls treated with normal rabbit IgG. Anti-IL-33 treatment also significantly decreased the serum levels of interferon-γ(IFN-γ),IL-6, IL-12, IL-33, and tumor necrosis factor-α (TNF-α). Moreover, anti-IL-33 treatment significantly downregulated the production of IFN-γ, IL-6, IL-12, IL-33, and TNF-α in ex vivo-stimulated spleen cells. Together, our results indicate that the IL-33-neutralizing antibody may provide a therapeutic strategy for RA by inhibiting the release of proinflammatory cytokines.